The Analysis of the Irrigation System in Ciwaringin Weir, Majalengka Regency - Fairus Sahara, Muhamad Fikri; Fathoni, Mohammad; Fazrurrakhmat, Muhammad Hafizh; Nurdiyanto, Nurdiyanto (International Journal of Social Service and Research, 2025)
The Ciwaringin Weir is located in Lame Village, Leuwimunding District, Majalengka Regency, West Java Province. It irrigates an area of approximately ±4364 hectares, comprising 3261 hectares in Majalengka Regency and 1103 hectares in Cirebon Regency. The core components of this irrigation system consist of primary and secondary canals. This study aims to evaluate the structural performance based on damage conditions, assess the current operational state, and determine the component weights of the canals and Ciwaringin Weir structures. Primary data were collected through field observations, while secondary data were obtained from relevant agencies, including the Cimanuk-Cisanggarung River Basin Organization (BBWS), UPTD PSDA Sumberjaya, and SUP Cimanuk Hilir-Kaliwedi. The research employed a qualitative method with a descriptive-inductive approach. The findings indicate that the performance of the primary and secondary canals of the Ciwaringin Weir, based on condition and function, is 36% in good condition, 37% moderate, and 27% damaged—indicating that the average condition is classified as moderately damaged. Meanwhile, the structural condition of the weir shows 34% good, 57% moderate, and 9% damaged, suggesting that the weir’s overall condition is still acceptable. Analysis comparing rainfall and discharge availability in the Ciwaringin Irrigation Area reveals that water availability exceeds demand, thus ensuring that the irrigation water needs in the area are fully met.